The contribution of two common shrub species to aboveground and belowground carbon stock in Iberian dehesas (Journal of Arid Environments, 2013)
Shrubs play an important role in water-limited agro-silvo-pastoral systems by providing shelter and forage for livestock, for erosion control, to maintain biodiversity, diversifying the landscape, and above all, facilitating the regeneration of trees. Furthermore, the carbon sink capacity of shrubs could also help to mitigate the effects of climate change since they constitute a high proportion of total plant biomass. The contribution of two common extensive native shrub species (Cistus ladanifer L. and Retama sphaerocarpa (L.) Boiss.) to the carbon pool of Iberian dehesas (Mediterranean agro-silvo-pastoral systems) is analyzed through biomass models developed at both individual (biovolume depending) and community level (height and cover depending). The total amount of carbon stored in these shrubs, including above- and belowground biomass, ranges from 1.8 to 11.2 Mg C ha 1 (mean 6.8 Mg C ha 1 ) for communities of C. ladanifer and from 2.6 to 8.6 Mg C ha 1 (mean 4.5 Mg C ha 1 ) for R. sphaerocarpa. These quantities account for over 20e30% of the total plant biomass in the system. The potential for carbon sequestration of these shrubs in the studied system ranges 0.10e1.32 Mg C ha 1 year 1 and 0.25e1.25 Mg C ha 1 year 1 for the C. ladanifer and R. sphaerocarpa communities’ respectively

Interspecific competition induces asymmetrical rooting profile adjustments in shrub-encroached open oak woodlands (Trees, 2012)
It is recognized that the extent of woody encroachment is increasing worldwide, but less is known concerning the likely altered below-ground structure of cooccurring plants. The aim of this study was to analyze the root system plasticity of three layers of vegetation growing together (trees, shrubs and pasture) and identify potential mechanisms of competition avoidance. Root morphology and distribution of trees, pasture and two contrasting shrub species (deep and shallow rooted) were studied in open oak woodlands of south-western Spain. Soil samples were obtained from paired adjacent plots, with and without shrubs, by taking soil cores to a depth of 3 m. Analysis of tree and pasture root systems in the presence of shrubs revealed signiﬁcant reductions in root biomass and consistent increases in speciﬁc root length. Additionally, root proﬁles changed substantially, becoming signiﬁcantly deeper for trees and shallower for pasture. In contrast, both types of shrub increased their root biomass when growing in competition, but without signiﬁcantly modifying their rooting proﬁle. Shrubs seem to be stronger competitors for below-ground resources than neighboring species. However, trees and pasture show clear plastic responses to shrub presence, irrespective of their rooting patterns, probably to minimize competitive interactions and maximize resource acquisition.

Past, Present and Future of Agroforestry Systems in Europe (Agroforestry - The Future of Global Land Use SE - 16, 2012)
Many traditional land-use systems in Europe involved agroforestry in the pre-industrial era, but, over the years, increased mechanization led to the develop- ment of increasingly specialized crop, animal and wood production systems. As a consequence, the area under agroforestry declined in many regions of Europe, and agroforestry systems became con fi ned to situations where understorey primary production is restricted due to cold temperatures (Boreal and Alpine areas) or drought (Mediterranean areas) and to plots that are hard to reach or too small for cultivation with modern machinery, as in Spain, Italy and the lower altitude mountain regions in southern and central Germany. On the whole, agroforestry continued to be practised only where it enabled farmers to obtain economic returns from lands that were otherwise relatively unproductive and mostly limited to silvopastoral practices. Since the mid-1990s, however, European policies have encouraged land management systems that combine production, environmental services (biodiversity, carbon sequestration, nutrient cycling and water quality) and social bene fi ts, and this has created a new interest in agroforestry systems. Today, the major agroforestry practices in Europe include silvopasture and silvoarable. However, the bene fi ts and opportunities offered by agroforestry can only be realized with substantial investments and coordinated efforts in research, education, knowledge transfer and appropriate national policies across Europe.

Silvoarable Systems in Europe – Past, Present and Future Prospects (Agroforestry Systems, 2006)
Mixed systems of agriculture incorporating combinations of trees and crops have formed key elements of the landscape of Europe throughout historical times, and many such systems continue to function in the present day. In many cases they represent formerly widespread traditional systems in decline and a number have already become extinct or exist only in a threatened state. The causes are both practical and economic. The agricultural subsidy regime within the European Union is presently unfavourable towards silvoarable practices, which has been a major factor in their recent decline. The silvoarable systems of Europe can be split into two classes according to location – northern Europe and the Mediterranean. The latter contains not only a greater area of silvoarable cultivation, but also a greater diversity of systems due to the broader range of commercial tree and crop species grown. In general, the systems of northern Europe are limited by light, whilst those of the Mediterranean are limited by the availability of water. Mixed systems of agriculture present an opportunity for future European rural development and have the potential to contribute towards the increased sustainability of agriculture and enhancement of biodiversity, whilst preserving landscapes that are both culturally important and aesthetically pleasing. A better understanding of the legacy of traditional silvoarable systems, combined with the formulation of a consistent deﬁnition and speciﬁc European policy towards them will be invaluable in ensuring that the beneﬁts of mixed agriculture are fully exploited in the future.

Soil nutrient status and forage yield at varying distances from trees in four dehesas in Extremadura, Spain (Silvopastoralism and Sustainable Land Management: Proceedings of an International Congress on Silvopastoralism and Sustainable Management Held in Lugo Spain, in April 2004, 2006)
The aim of this study was to understand the effect of holm-oak (Quercus ilex) on the soilnutrient concentration and its consequence on the yield of understory forage (Avena sativa) in four dehesas of CW-Spain. The soils of the dehesas varied in soil fertility (chromic Luvisols and Achrisols, and eutric Leptosols). Forage dry-matter yields were determined from 1-m2 sample plots at distances ranging from 2 to 20 m from the tree (9 trees per farm and year). Soil samples (0-30 cm depth) were also collected from the same sampling locations, and were analysed for pH, Electrical Conductivity, organic C, CEC, total-N, available N and base cations. Soil analysis results showed that the most of the values increased in the vicinity of the tree: organic C, total-N, CEC and exchangeable Ca2+ and K+. Differences in forage yield were mainly explained by fertilization dosage, light availability (estimated from Montero and Moreno, 2004) and soil CEC. In more fertile soils, forage production was negatively effected by the presence of the trees, as a consequence of light reduction (Competence), while in more oligotrophic soils, forage production was positively affetced by trees (Facilitation).

MYCOLOGICAL STUDY IN THE NATURAL-PARK-OF-THE-ALCORNOCALES (ANDALUSIA, SPAIN) .1. AGARICALES (CRYPTOGAMIE MYCOLOGIE, 1994)
This work includes the first results about the Agaricales s. lato collected mostly in Quercus suber forest in the Natural Park of the Alcornocales (Andalucia, Spain). The most outstanding taxa are: Hebeloma danicum, H. sacchariolens var. pallidoluctuosum, H. mesophaeum var. pallidum, H. sacchariolens var. pallidoluctuosum, Lactarius luteolus, Pluteus plautus, Russula bresadoliana, R. fragrantissima, R. graveolens var. megacantha, R. graveolens var. purpurata. A microscopical study under the S.E.M. of the spore ornamentation of the most interesting taxa is given.